Предмет: Алгебра,
автор: 532622
упростите выражение (1-cos^2α)tg^2α+1-tg^2α
Ответы
Автор ответа:
0
я не поняла но ажется так
но это наверно другое решение но сделала
1-cos^2 α)/(sin^2 α)+1/(sin^2 α*(1+tg^2 α)) 1-cos^2 α=sin^2α 1+tg^2 α=1/(cos^2a) (1-cos^2 α)/(sin^2 α)+1/(sin^2 α*(1+tg^2 α))=sin^2α/(sin^2 α)+ + 1/(sin^2 α*(1/cos^2a)=1+cos^2a/sin^2 α=1+ctg^2a=1/sin^2 a
но это наверно другое решение но сделала
1-cos^2 α)/(sin^2 α)+1/(sin^2 α*(1+tg^2 α)) 1-cos^2 α=sin^2α 1+tg^2 α=1/(cos^2a) (1-cos^2 α)/(sin^2 α)+1/(sin^2 α*(1+tg^2 α))=sin^2α/(sin^2 α)+ + 1/(sin^2 α*(1/cos^2a)=1+cos^2a/sin^2 α=1+ctg^2a=1/sin^2 a
Похожие вопросы
Предмет: МХК,
автор: Аноним
Предмет: Алгебра,
автор: titovetslinchik
Предмет: Математика,
автор: royaaramazanova8
Предмет: Биология,
автор: DrKoks
Предмет: Математика,
автор: вл2д